Propuesta de diseño de un sistema de energía solar fotovoltaica. Caso de aplicación en la ciudad de Bogotá - Salamanca-Avila, Sebastian (Revista Científica, 2017)
Solar energy is a renewable resource, that is, it is always available, it is not exhausted, and you can take advantage of that energy from the sun at any time thanks to its storage. The difficult environmental conditions, pollution and, on the other hand, the technological advance in the development of increasingly efficient solar cells, has contributed to the current promotion of the use of renewable energy such as solar energy. In addition, the use of these systems has increased since the level of pollution is very low and installation costs are recovered by reducing the billing of energy consumption, provided by utilities. Therefore, the use of photovoltaic systems is a topic of great interest today, and to implement this type of isolated photovoltaic systems in the city of Bogota is possible.